1986
DOI: 10.2527/jas1986.6361759x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Misidentification on the Estimation of Breeding Value and Heritability in Cattle1

Abstract: For daughter groups of 15 test bulls, controls of paternity were performed by using blood group factors and biochemical polymorphisms. Data of incorrectly assigned daughters influenced the estimation of breeding values, heritabilities and correlations for milk performance traits. Formulae are given that show the effects of variable misidentification rates on estimation of breeding values, selection intensities, heritabilities, and genetic gains. For example, for milk fat yield, the genetic gains drop at a misi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
3
7

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 0 publications
4
60
3
7
Order By: Relevance
“…New reputed daughters assigned to high-merit bulls through random replacement were expected to be of generally lower merit than the true progeny that were replaced. Estimated annual genetic trends decreased by 11 to 15% overall (Table 3), which was similar to results from the simulation study of Gelderman et al (1986) but more than found through simulation by Israel and Weller (2000). The observed decrease in annual trend was larger than Israel and Weller's (2000) probably because truly top bulls would not have been used as heavily here, had selection been based on their biased genetic evaluation.…”
Section: National Evaluationssupporting
confidence: 75%
See 3 more Smart Citations
“…New reputed daughters assigned to high-merit bulls through random replacement were expected to be of generally lower merit than the true progeny that were replaced. Estimated annual genetic trends decreased by 11 to 15% overall (Table 3), which was similar to results from the simulation study of Gelderman et al (1986) but more than found through simulation by Israel and Weller (2000). The observed decrease in annual trend was larger than Israel and Weller's (2000) probably because truly top bulls would not have been used as heavily here, had selection been based on their biased genetic evaluation.…”
Section: National Evaluationssupporting
confidence: 75%
“…Paternity errors are expected to bias estimation of genetic parameters (Van Vleck, 1970b), breeding values of individual animals (Israel and Weller, 2000;Van Vleck, 1970a), and genetic progress (Gelderman et al, 1986;Van Vleck, 1970a). Van Vleck (1970b) also showed that bias increased as the proportion of records with errors increased.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies [5,7,14] show that the misidentification rate in cattle pedigrees varies between about 3 and over 20%. Even in Lipizzan horse pedigrees where a great importance is attached to correct pedigree recording, a small number of pedigree errors has been revealed by mtDNA analysis [10].…”
Section: Correctness Of Pedigreesmentioning
confidence: 99%